TRANSFORMING RELIGIOUS IDENTITY THROUGH PATRIOTISM-BASED ISLAMIC EDUCATION: A SOCIAL REINTEGRATION MODEL AT YAYASAN LINGKAR PERDAMAIAN - Ali Rusdiyanto (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2022)
This study examines the transformation of religious identity through Islamic education based on patriotism as a model of social reintegration at Yayasan Lingkar Perdamaian (YLP). It departs from the premise that deradicalization should not be limited to disengagement from extremist networks but must involve a deeper reconstruction of religious identity toward inclusivity and national commitment. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using thematic-interactive procedures. The findings reveal a three-stage transformation process: (1) deconstruction of exclusivist identity through reflective dialogue and moderate Islamic education; (2) reconstruction of a religio-national identity through the internalization of patriotic values; and (3) social reintegration through community participation and social recognition. The study demonstrates that Islamic education grounded in patriotism functions as both an epistemological and social medium for aligning religious commitment with national belonging. Theoretically, this research proposes a model of identity transformation as an alternative framework for education-based deradicalization studies.